2004
DOI: 10.1152/ajpgi.00056.2004
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Alcoholic Liver Disease II. Minireview: molecular mechanisms of alcoholic fatty liver

Abstract: Alcohol has long been thought to cause fatty liver by way of altered NADH/NAD+ redox potential in the liver, which, in turn, inhibits fatty acid oxidation and the activity of tricarboxylic acid cycle reactions. More recent studies indicate that additional effects of ethanol both impair fat oxidation and stimulate lipogenesis. Ethanol interferes with DNA binding and transcription-activating properties of peroxisome proliferator-activated receptor-α (PPARα), as demonstrated with cultured cells and in ethanol-fed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
158
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 199 publications
(165 citation statements)
references
References 25 publications
7
158
0
Order By: Relevance
“…AMPK is known to downregulate fatty acid synthesis via reduced SREBP-1c expression 28 or ACC inactivation, 29 and reduced expression or activity of AMPK is implicated in alcoholic fatty liver. 30 However, neither AMPK ␣-subunit (AMPK␣) nor the activated form of AMPK, phosophorylated AMPK (p-AMPK), was changed in fatty livers of our obese mice (Fig. 5A).…”
Section: Resultsmentioning
confidence: 81%
“…AMPK is known to downregulate fatty acid synthesis via reduced SREBP-1c expression 28 or ACC inactivation, 29 and reduced expression or activity of AMPK is implicated in alcoholic fatty liver. 30 However, neither AMPK ␣-subunit (AMPK␣) nor the activated form of AMPK, phosophorylated AMPK (p-AMPK), was changed in fatty livers of our obese mice (Fig. 5A).…”
Section: Resultsmentioning
confidence: 81%
“…The observation that mice deficient in TNF receptor 1 or endotoxin binding-signalling molecules develop less steatosis than wild-type animals (Arteel, 2003) suggests the possible involvement of oxidative mechanisms in the signals leading to Kupffer cell activation by endotoxins and/or in the metabolic effects of TNF-a (Dandona et al 2004). Nonetheless, it cannot be excluded that oxidative stress might also contribute to the effects of ethanol on the regulation of lipid metabolism by either the PPARa or the sterol regulatory element-binding protein 1 (You & Crabb, 2004). The induction of oxidative stress within liver mitochondria is associated with the collapse of mitochondrial membrane potential and the onset of mitochondrial permeability transition (MPT) (Hoek et al 2002).…”
Section: Oxidative Mechanisms and Mitochondrial Damage By Ethanolmentioning
confidence: 99%
“…Most studies on alcoholic hepatic steatosis have focused on the ability of ethanol to shift the redox state in the liver and to inhibit fatty acid oxidation [3,4] . Indeed, previous studies have shown the repression of some enzymes involved in fatty acid oxidation and induction of lipogenic enzymes in ethanol-fed animals [2,5] . The de novo synthesis of fatty acids in the liver was shown to increase with ethanol feeding in conjunction with the induction of adipogenic enzymes, including peroxisome proliferator-activated receptor alpha (PPAR alpha) and/or sterol regulatory element binding protein 1 (SREBP-1) [2,6] .…”
Section: Introductionmentioning
confidence: 96%
“…Alcohol is known to impair fat oxidation and to stimulate lipogenesis in the liver [2,3] . Thus, alcohol consumption can lead to the development of hepatic steatosis.…”
Section: Introductionmentioning
confidence: 99%